Sistem Informasi Penerimaan Siswa Baru di SMK Assanadyah Palembang Berbasis Web - muhammad alfandy romadhon; Hadi Syaputra; Afriyudi; Fitri Purwaningtias (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
The process of accepting new students is the earliest gate of learning activities that students will enter at a school of their choice. Assanadyah Palembang Vocational School is one of the vocational schools in the city of Palembang which is still carrying out the conventional new student admissions process, namely by using a registration form for making new student admission reports by relying on the main book as a data storage medium. The method used in developing the new student admission system uses web engineering which consists of several stages, namely Customer Communication, Modeling, Planning, Construction and Delivery and Feedback. The test results using black box testing with the aspect of functionality obtained a score of 100%, for testing the usability aspect the results obtained 85% and it was stated that this website is useful, and can present the information needed accurately, easily and efficiently with an online computerized system.